Young College Students’ Perception of DINESERV: A Study of On-Campus Dining in the USA - Hyunsuk Choi (Faculty of tourism and hospitality management, 2021)
Purpose – The purpose of this research is to better understand why college students in the USA eat on-campus. Also, this research aims to compare highly satisfied and low satisfied groups in terms of their on-campus dining experiences and behaviors and to understand what values college students are currently satisfied with and what they expect from their on-campus dining. Design – A survey design was implemented in this study. The sample for this research study is any college students who have eaten at on-campus dining facilities within the last 3 months. Methodology – Cluster analysis, correlation, and t-test were utilized for data analysis. The twostep clusters method was used to cluster groups based on the mean values of DINESERV. Approach – The validity of DINESERV for on-campus dining settings was examined, as well as examining the behavior and perception of Generation Y and Z on on-campus dining. Findings – In both clusters, Assurance was the factor with the highest correlation coefficient value, while Tangible ranked last among the five DINESERV factors. The other dimensions of DINESERV were also very important to the young college students, as indicated by the high correlation coefficients. Originality of the research – This research examines the validity of DINESERV in on-campus dining settings in the United States. The uniqueness of this study lies in the sample: young college students, Generation Y and Z.